MANAGERIAL ECONOMICS – ESSENTIAL ACTIONS AND CONNECTIONS - VĂDUVA CECILIA ELENA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
A common definition of economics is that it is the study of the processes of production, distribution and consumption of goods and services. Another definition refers to the analysis of choices related to the use of limited resources. The first definition suggests that the economy encompasses any type of business, non-profit organization or administrative entity. The second definition emphasizes that economics is central to the activities of managers in these organizations. The objective of managerial economics is to provide an economic vocabulary and reasoning to support improved management decision-making. Most readers are probably familiar with two distinct perspectives on the study of economics: microeconomics and macroeconomics. Microeconomics focuses on the analysis of phenomena related to goods and services from the point of view of individual decision-making entities such as households and companies. On the other hand, macroeconomics examines the same phenomena at an aggregate level, for example, total consumption and production in a given region. Microeconomics and macroeconomics both have their importance. Microeconomic analysis is crucial to understanding the behavior of individual entities in an economy. However, to understand the complex interactions between numerous households and firms, it would be too complicated to rely only on descriptions of individual units. The macroeconomic perspective provides tools and theories that make it easier to understand the overall behavior of an economy. The purpose of managerial economics is to use economic principles to optimize managerial decisions in an organization, which makes most of the content of this discipline oriented towards microeconomic aspects. However, given that managers must take into account the context in which they operate, which also includes the general economy, knowing how to interpret and forecast macroeconomic indicators becomes essential for an informed managerial decision.